2011
DOI: 10.1590/s0102-86502011000600012
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ionizing radiation on bone neoformation: histometric study in Wistar rats tibiae

Abstract: PURPOSE:Comparing the ionizing radiation effects on bone neoformation of rats tibiae previously submitted to radiotherapy with a single dosage of 30Gy with the contralateral tibiae that have received secondary radiation. METHODS:In thirty male Wistar rats, 30 days before surgical procedure when round defects would be created on the bone, the right tibia was irradiated with 30Gy and the left tibia received a calculated secondary radiation dose of 7Gy. Sacrifices were performed after 4, 7, 14, 21, 56 and 84 post… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 14 publications
0
2
0
1
Order By: Relevance
“…In the present study, histomorphometric analyses showed lower bone matrix levels in C30 compared with IR30. Some studies have reported that irradiation changed the bone turnover, significantly reduced vessel diameter [18] and could decrease remodeling process, which showed more bone matrix formation [24]. Thus, the higher matrix values shown in IR30 probably reflected changes and delay in the bone remodeling process.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, histomorphometric analyses showed lower bone matrix levels in C30 compared with IR30. Some studies have reported that irradiation changed the bone turnover, significantly reduced vessel diameter [18] and could decrease remodeling process, which showed more bone matrix formation [24]. Thus, the higher matrix values shown in IR30 probably reflected changes and delay in the bone remodeling process.…”
Section: Discussionmentioning
confidence: 99%
“…As demonstrated for high doses in rodent models, damage to bone-forming cells, vasculature, or an impaired hormone balance can be responsible for the loss of bone mass. This is caused by inflammation, a restricted nutrient supply and a reduced bone neoformation ( 14 , 18 ). For lower doses, no such harmful effects have been anticipated ( 19 ).…”
Section: Introductionmentioning
confidence: 99%
“…A radiação ionizante utilizada em diagnósticos e tratamentos é um dos elementos que influenciam no processo de reparo ósseo . As alterações a nível celular e vascular provocadas por altas doses de radiação no tecido ósseo resultam na neoformação de um tecido desorganizado e rico em tecido fibrótico (Barth et al, 2011;Lucatto et al, 2011;Bartlow et al, 2018). Após a exposição à radiação ionizante, ocorrem alterações vasculares que se iniciam com o aumento da permeabilidade das células endoteliais, resultando em disfunção endotelial (Baselet et al, 2018).…”
Section: Introdução E Referencial Teóricounclassified